Ponta Grossa 200 Years: An Analysis from the Concept of Cultural Democracy - Martins Machado, Daiani (2024)
This article presents an analysis of the 200th anniversary celebrations of the city of Ponta Grossa-PR in line with the concept of cultural democracy. The method used was the hypothetical-deductive approach, with bibliographic, historical, and documentary research. It was assessed that the Municipal Government organized several festive events throughout the year to commemorate the bicentennial, aiming to reach diverse audiences and meet various demands. However, it was observed that these events, for the most part, did not manage to broadly benefit the population according to the elements of the concept of cultural democracy. It is concluded that there is a hierarchy in cultural decision-making, which at times believes it is benefiting citizens, but excludes peripheral groups, failing to provide opportunities for their expressions or interests. Decentralization also does not occur satisfactorily, as the government focuses its actions on universal access through economic emphasis, while the crucial point is the symbolic one.